# algebraic expressions

• Jan 21st 2009, 12:13 PM
Leona_Marie
algebraic expressions
-(12/-3) +5(2) = -4+10 =6 my study book tells me this equation = -6 can anyone tell me why and how this equation could = -6
• Jan 21st 2009, 01:14 PM
earboth
Quote:

Originally Posted by Leona_Marie
-(12/-3) +5(2) = -4+10 =6 my study book tells me this equation = -6 can anyone tell me why and how this equation could = -6

$-\left(\frac{12}{-3}\right) + 5 \cdot (2) = -(-4) + 10 = 4 + 10 = 14$

Could it be that the original question reads:

$-\left(\frac{12}{-3}\right) + 5 \cdot (-2) = -(-4) - 10 = 4 - 10 = -6$
• Jan 21st 2009, 01:37 PM
Leona_Marie
Quote:

Originally Posted by earboth
$-\left(\frac{12}{-3}\right) + 5 \cdot (2) = -(-4) + 10 = 4 + 10 = 14$

Could it be that the original question reads:

$-\left(\frac{12}{-3}\right) + 5 \cdot (-2) = -(-4) - 10 = 4 - 10 = -6$

earthboth, what if we did-(12/-3 +2)^2
• Jan 21st 2009, 11:43 PM
earboth
Quote:

Originally Posted by Leona_Marie
earthboth, what if we did-(12/-3 +2)^2

Of course, that is possible too. But there are some more possibilities, for instance:

$-\left(\frac{12}{-3} +5(2)\right) = -(-4+10) = -6$
• Jan 22nd 2009, 08:04 AM
Leona_Marie
Quote:

Originally Posted by earboth
Of course, that is possible too. But there are some more possibilities, for instance:

$-\left(\frac{12}{-3} +5(2)\right) = -(-4+10) = -6$

thank you very much,